Determination of Workload, Work Stress, and Authotarian Leadership Style on Performance Performance - Febrian, Wenny; Silva Nurhalisah (Dinasti International Journal of Digital Business Management, 2024)
Abstract: This study aims to find out and analyze the effect of workload, work stress, and authoritarian leadership style on employee performance. Less than optimal employee performance is affected by many employees feel burdened by the heavy workload. This makes some employees feel pressured, so they don't have enough time to complete work and cause stress. Workload and stress can be influenced by the leadership style of the company's management. This research includes quantitative descriptive research. The measurement scale used in this study is the Likert scale. Samples were taken using saturated sampling method, namely the entire population was used as a sample, totaling 34 people. This research was conducted for 3 months. Data collection techniques in this study were interviews, observation and questionnaires. These results indicate that: (H1) Workload has no effect on Employee Performance with a value of Sig.0.717>0.05 and a calculated t value of 0.366<2.042 (H2) Work Stress has an effect on Employee Performance with a value of Sig. 0.015<0.05 and calculated t value 2.585>2.042 (H3) Authoritarian Leadership Style has no effect on Employee Performance with a value of 0.767>0.05 and calculated t value -0.298<2.042. The F Test results show that H4 is accepted with a Sig value. 0.023<0.05 and f count 3.653>2.91.